Allelopathic Effect of Santa Maria (Parthenium hysterophrous) Mulch on Growth and Yield of Soybean (Glycine max) - HUSSAIN,S. (2016)
ABSTRACT To determine the effect of Santa Maria (Parthenium hysterophrous) mulch on growth and yield of soybean, a study was conducted at the Department of Agronomy, Faculty of Agriculture, The University of Poonch, Rawalakot, Azad Jammu and Kashmir. The experiment was conducted in the laboratory as well as in the greenhouse. Parthenium surface mulch and soil incorporation was practiced at different levels in laboratory as well as in greenhouse. Higher allelopathic potential was found by the treatments of Parthenium soil incorporation, especially when soil incorporation of Parthenium herbage @ 5 ton ha-1 was practiced. This could be because of the presence of soil moisture that enhanced the decomposition of Parthenium therefore, retarded the growth and other parameters. The study showed that Parthenium hysterophrous considerably reduced the emergence, seedling growth and yield of soybean.